Coherence of Elsässer Variables in the slow solar wind from 0.1 au to 0.3 au - Wu, Honghong; Yang, Liping; Huang, Shiyong (Frontiers in Astronomy and Space Sciences, 2024)
The highly Alfvénic fluctuations (AF) and magnetic-velocity alignment structures (MVAS) are two distinguished components in the near-Sun slow solar wind observed by Parker Solar Probe. The amplitudes of the Elsässer Variables z ± of AF and MVAS show distinct features. However, how these fluctuations contribute to the slow solar wind turbulence remains unknown. Here we investigate the coherence between z + and z − for the first time using the Parker Solar Probe measurements with a high resolution 0.8738 s in the slow solar wind from 0.1-0.3 au. We find that the coherence spectra of z + and z − in the perpendicular directions for MVAS are remarkable higher than that for AF, in particular at large scale. There exists a break around 10 d i (d i is the ion inertial length) where the coherence decreases to a lower level for MVAS. A bump around 10 d i appears on the coherence spectra of all three components for AF. The coherence of z + and z − may relate to the possible nonlinear interactions reflected by the the time series, the power spectra, and the self-correlation functions. These results help to understand the roles of AF and MVAS in the slow solar wind turbulence.